Work Resilience Based On Career Experience, Employee Wellbeing, And Organizational Support As An Implementation Of SDG’s No. 8: Decent Work And Economic Growth - Rangga Mahesa; Sigit Hermawan; Vera Firdaus (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The electricity generation industry plays a vital role in supporting economic growth and ensuring a stable energy supply. PT PLN (Persero) PLTU Asam Asam is one of the coal-fired power plants contributing significantly to the national electricity grid. Given the operational challenges and the need for workforce resilience in this sector, this study aims to examine the influence of career experience, employee well-being, and organizational support on work resilience among employees at PLTU Asam Asam. This research adopts a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to employees involved in operations, maintenance, and management. The findings indicate that career experience and employee well-being significantly impact work resilience, whereas organizational support has a weaker but still significant influence. The study highlights that employees with extensive career experience and high well-being levels tend to have better work resilience. Moreover, strong organizational support contributes to employees' ability to adapt and overcome workplace challenges. The study provides insights into human resource management practices in the energy sector, emphasizing the importance of career development programs, employee well-being initiatives, and organizational support systems in enhancing workforce resilience.